The Problems Encountered by Teachers in Teaching Procedure Text - Rahmawati, Movi Riana; Listiyani, Anni; Damayanti, Sri (ENGLISH JOURNAL, 2016)
Writing is one of the skills in English that needs to be learned, practiced and mastered by students. In learning English, there are various genre which should be learnt. The genre are recount text (spoof), procedure text, narrative text, descriptive text, news item, report text, analytical exposition text, hortatory exposition text, explanation text, discussion text, review text and anecdote text. Procedure text is an important for students to improve their English skill. In teaching learning process the teachers often face some problems when they are teaching procedure text such as what’s the problem encountered by teacher in teaching procedure text, and how do teachers facilitate students in the use of temporal conjunction/connecting time word. Therefore, teachers have to find way to make their students feel interested when they study in their class. The aim of this research is to find the problem encountered by teacher in teaching procedure text. The writers used qualitative research. The writers applied observation and interview used as instruments to get the information directly from the teachers in the process of teaching procedure text. The result of the research shows that the teachers have some problems in media and teaching material, very limited insight and knowledge of students about environmental conditions, and the lack of English vocabulary. The teachers have important roles in teaching procedure text; the teachers who act as the facilitators in this study should motivate the students to practice the procedure text more. They should use interesting techniques so that students will enjoy and be brave to come forward to present material about procedure text.